Применение гибких носителей при сборке кремниевых детекторов - Perevertaylo, V. L.; Zhora, V. D.; Grunyanska, V. P.; Pugatch, V. M.; Tuchynsky, I. A; Shkirenko, E. A. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The prospects of applying flexible carrier technology of the 'aluminum–polyimide' type for assembling detectors of various purposes, including silicon microstrip detectors, are demonstrated. Actual designs and examples of assembling different detector units using flexible carrier technology are presented, in particular microcables, adapters, ribbons, and interconnections. The advantages of this technology are considered in comparison with wire connections in detectors with a large number of outputs and a small pitch.